Capital Market Union and residential capitalism in Europe: Rescaling the housing-centred model of financialization - Rodrigo Fernandez; Manuel Aalbers (Finance and Society, 2017)
This article examines the effects of implementing the proposals of the European Commission to institute a Capital Market Union (CMU) on the diverse landscape of residential capitalism in Europe. The CMU will bypass existing national institutional blockades that left core countries of the Eurozone, namely Germany, France and Italy, largely untouched by the housing-centred financialization that developed in countries like Spain, Ireland, the UK and the Netherlands. It is widely acknowledged that the rise in securitized mortgage debt contributed to the global financial crisis. As part of the CMU, the new European Commission is promoting mortgage securitization throughout the EU and thereby rescaling the political economy of housing finance that was hitherto rooted in national, institutional models. We argue that countries which 'missed' the previous housing boom will not be able to prevent future housing-centred financialization. CMU thus signifies a spatial expansion of the debt-led accumulation model.
Keywords: 300; Financialization; securitization; housing; Capital Market Union; mortgage markets